Challenges and Possibilities for Truth and Reconciliation In Teacher Education: An Engagement with the Literature - Tupper, Jennifer Anne; Omoregie, Abiemwense Edokpayi (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
This article delves into the evolving landscape of teacher education within the context of truth and reconciliation, acknowledging the profound role education has played in perpetuating colonial violence against Indigenous peoples. To assess reconciliation efforts in teacher education, a targeted search was undertaken, which resulted in an inductive thematic analysis of 36 scholarly works and the emergence of five overarching themes: anti-racist/anti-oppressive perspectives, decolonization, critical forms of pedagogy/narrativity, indigenization, and historical thinking. The analysis provides valuable insights and highlights challenges of advancing truth and reconciliation in education including the need for a paradigm shift within teacher education programs, urging them to adopt community-focused, land-based, and decolonizing approaches. By aligning with the spirit and intent of truth and reconciliation, and as the studies demonstrate, teacher education has the potential to contribute significantly to advancing the process of healing, justice, and mutual understanding in the journey toward a more equitable and harmonious future.